Patterns of Antibiotic Nonsusceptibility Among Invasive Group A Streptococcus Infections—United States, 2006–2017. (25th June 2021) - Fay, Katherine; Onukwube, Jennifer; Chochua, Sopio; Schaffner, William; Cieslak, Paul; Lynfield, Ruth; Muse, Alison; Smelser, Chad; Harrison, Lee H; Farley, Monica; Petit, Susan; Alden, Nisha; et al.
Abstract: Background: Treatment of severe group A Streptococcus (GAS) infections requires timely and appropriate antibiotic therapy. We describe the epidemiology of antimicrobial-resistant invasive GAS (iGAS) infections in the United States (US). Methods: We analyzed population-based iGAS surveillance data at 10 US sites from 2006 through 2017. Cases were defined as infection with GAS isolated from normally sterile sites or wounds in patients with necrotizing fasciitis or streptococcal toxic shock syndrome. GAS isolates were emm typed. Antimicrobial susceptibility was determined using broth microdilution or whole genome sequencing. We compared characteristics among patients infected with erythromycin-nonsusceptible (EryNS) and clindamycin-nonsusceptible (CliNS) strains to those with susceptible infections. We analyzed proportions of EryNS and CliNS among isolates by site, year, risk factors, and emm type. Results: Overall, 17 179 iGAS cases were reported; 14.5% were EryNS. Among isolates tested for both inducible and constitutive CliNS (2011–2017), 14.6% were CliNS. Most (99.8%) CliNS isolates were EryNS. Resistance was highest in 2017 (EryNS: 22.8%; CliNS: 22.0%). All isolates were susceptible to β-lactams. EryNS and CliNS infections were most frequent among persons aged 18–34 years and in persons residing in long-term care facilities, experiencing homelessness, incarcerated, or who injected drugs. Patterns varied by site. Patients with nonsusceptible infections were significantly less likely to die. The emm types with >30% EryNS or CliNS included types 77, 58, 11, 83, and 92. Conclusions: Increasing prevalence of EryNS and CliNS iGAS infections in the US is predominantly due to expansion of several emm types. Clinicians should consider local resistance patterns when treating iGAS infections. Abstract : Prevalence of invasive group A Streptococcus (iGAS) infections nonsusceptible to erythromycin and clindamycin in the US rose over a 12-year period. The increase was predominantly due to expansion of several emm types. Clinicians should consider local resistance patterns when treating iGAS infections.